Inhibition of the SUV4-20 H1 histone methyltransferase increases frataxin expression in Friedreich's ataxia patient cells - Vilema Enriquez, MG; Quinlan, R; Kilfeather, P; Mazzone, R; Saqlain, S; Del Molino Del Barrio, I; Donato, A; Corda, G; Li, F; Vedadi, M; Németh, AH; Brennan, PE; et al. (American Society for Biochemistry and Molecular Biology, 2020)
The molecular mechanisms of reduced frataxin (FXN) expression in Friedreich's ataxia (FRDA) are linked to epigenetic modification of the FXN locus caused by the disease-associated GAA expansion. Here, we identify that SUV4-20 histone methyltransferases, specifically SUV4-20 H1, play an important role in the regulation of FXN expression and represent a novel therapeutic target. Using a human FXN–GAA–Luciferase repeat expansion genomic DNA reporter model of FRDA, we screened the Structural Genomics Consortium epigenetic probe collection. We found that pharmacological inhibition of the SUV4-20 methyltransferases by the tool compound A-196 increased the expression of FXN by ∼1.5-fold in the reporter cell line. In several FRDA cell lines and patient-derived primary peripheral blood mononuclear cells, A-196 increased FXN expression by up to 2-fold, an effect not seen in WT cells. SUV4-20 inhibition was accompanied by a reduction in H4K20me2 and H4K20me3 and an increase in H4K20me1, but only modest (1.4–7.8%) perturbation in genome-wide expression was observed. Finally, based on the structural activity relationship and crystal structure of A-196, novel small molecule A-196 analogs were synthesized and shown to give a 20-fold increase in potency for increasing FXN expression. Overall, our results suggest that histone methylation is important in the regulation of FXN expression and highlight SUV4-20 H1 as a potential novel therapeutic target for FRDA.